Structural biomass and by compartments of Pinus patula regeneration in clearcutting sites - Rodríguez-Ortiz, Gerardo; García-Aguilar, Juan Ángel; Leyva-López, José Cristóbal; Ruiz-Díaz, César; Enríquez-del Valle, José Raymundo; Santiago-García, Wenceslao (Instituto de Ecología, A.C., 2019)
Biomass measurements allows knowledge about processes like matter and energy movement, carbon sequestration and storage, among others. Therefore, the objective was to analyze the distribution of structural components of Pinus patula biomass in the green twig stage, as well as the compartments in clearcutting stripe sites at Ixtlán de Juárez, Oaxaca. In 2014, nine sites of 400 m2 each were located using selective sampling and tree inventory was applied. Destructive sampling of 90 trees in the green twig stage was used in order to obtain samples of each structural component, which were subsequently analyzed by regression, to estimate the biomass content per tree and unit of area. The biomass of other compartments (necromass, mulch, bushes and litter fall) of the site was quantified. Variance analysis and mean tests (Tukey, 0.05) were applied for the biomass compartments according to the tree density. The regression models showed adjustments between 0.79% and 97% by structural component and total tree, using inventory variables (diameter at breast height and total height). The high recommended density (> 1500 trees ha-1) presented the largest biomass stores in stem (8048.3 kg ha-1), branches (141.3 kg ha-1), leaves (146.2 kg ha-1) and roots (1350.0 kg ha-1). The clearcutting silvicultural treatment at seven years of its application favors the natural regeneration of the forest with 11.91 t ha-1 of biomass distributed in different compartments.